Evaluate the Shear Bond Strength for Alkasite in Comparison with other Esthetic Restorative Materials - Mohammed Wajeeh Shackori; Nadia H Hasan; Ammar Abdulghani Qasim; Aous A. Abdulmajeed (University of Mosul, College of Dentistry, 2024)
Aims: To assess and compare the shear bond strength of alkasite restoration, as well as, to compare the shear bond strength between alkasite with and without bonding. Materials and methods: Twenty-five permanent maxillary premolars were used in which, with diamond disks, their buccal surfaces were flattened until a clear superficial dentinal surface could be seen. Samples were randomly assigned to five groups (n=5). Group 1: alkasite without adhesive, Group 2: alkasite with adhesive, Group 3: Nanohybrid composite, Group 4: Glass ionomer cement, and Group 5: Resin modified glass inomer cement. Following the recommendations of the manufacturers, cylinders of the five restorative materials were bonded to the buccal surfaces. Following 24 hours storage at 37°C. The evaluation of shear bond strength was employed by the use of the universal testing machine. Under a stereomicroscope (×20), the fracture mode was determined. Data were statistically analyzed using a nonparametric independent sample Kruskal-Wallis test at the confidence level of 95%. Result: There were statistical differences among groups and there was a significant difference between the alkasite with and without bonding. Conclusion: Alkasite with bonding showed a higher shear bond strength in comparison with GIC and resin-modified GIC, but still lower than that of nanohybrid composite Moreover, the shear bond strength of alkasite highly improved with the use of bonding.